Videographic experiences in times of pandemic - Sarzi Ribeiro, Regilene Aparecida [UNESP]; ACM (Assoc Computing Machinery, 2021)
Video calls, video conferences, video art, video dance, video poetry and thus, with that eagerness to see and hear the other, we live in audiovisual mediation devices that do not stop associating with this or that platform or channel in digital culture. When, in 2020, the situation of social isolation imposed on the world by the COVID-19 pandemic broke out, only the audiovisual image continued to travel between media, to transit in the interstices, across borders, towards the meeting with the other, as a being of passage and of uncertain nature and identities, adrift through networks, whether as an archive or in real time. In this context, it is worth reflecting on video as a media-image and metaphor of contemporary man himself: borderless, nomadic, in constant flux, which, even without being able to transit, surpassed technological mediation, becoming an omnipresence whether in video files or video in real time here we name videonomadism. The phenomenon of telepresence, already experienced, is here expanded to think of the video image as a symbol of the diaspora image, drift. It is about thinking video as a contemporary cultural phenomenon aiming to describe the complexity of the videographic system. For this, we opted for decolonial approaches whose critical stance and contrary to the hegemonic and canonical systems of the history of art and culture, have significantly contributed to the production of other perspectives on phenomena such as media, technology, and art, and by extension as we intend with this research, promote new readings of video art. The basic reasoning was mainly related to the decolonial approach of Latin American authors such as Zulma Palermo [8] and Boaventura de Souza Santos [9], having as object of study, the video Small fragments of a suspension machine with interstices by Paloma Oliveira and Mateus Knelsen who was part of the first Pink Umbrellas Art Residency Festival, curated by artists Mirella Brandi and Mueptemo [12], whose video works are audiovisual site specifics created collaboratively by artist duos and exclusively for the Internet.
Keywords: Audiovisual; Videoarte; Video e Pandemia; Pink Umbrellas Art Residency Festival